Voicing the Voiceless in Geeta Nagabhushana’s Novel Dhange - S. Kathyayini (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The evolution of Dalits in literature’s trajectory reveals its capacity for both revolutionary and reactionary actions. The harsh and cruel reality of the existence of the metaphorical Caliban is reflected in Dalit literature’s themes. This is an effort to produce an entirely novel form of writing representative of Dalit writers who believe they can overcome their exclusion and lack of voice. Due to their long history as victims of patriarchal society, Dalit women still have relatively little freedom concerning human rights. Human torture, rapes, killings, and other murders are often the result of the higher castes’ steadfast resistance to their efforts to seize their rights. These are indications that the subalterns are in threat of being killed again, threats caused by the authority of the upper caste. Horrifying representations of concrete emerge in Dalit alter-texts. The extent of violence against women of Dalit origin remains unrecognized and unheard. Dalit literature seeks to reveal the evil and hypocrisy of the privileged classes and to protest against the existing system of hierarchy that is based on injustice. A journey from idealism to reality based on real-life experiences must be started promptly. Based on a novel Dhange by Geeta Nagabhushan, a Kannada writer, this article explores the impediments to their freedom and the reasons for their choice to speak up.